The Implementation of Internal Control based on Tri Kaya Parisudha Concept and Accounting Fraud Prevention in Hotel Industry - Julianto, I Putu; Pasek, Nyoman Suadnyana (Universitas Pendidikan Ganesha, 2021)
The present research aimed at (1) to investigate Tri Kaya Parisudha concept in the internal control of accounting fraud potential prevention effort; (2) To investigate the obstacles faced in the implementation of the Tri Kaya Parisudha concept as the prevention effort of accounting fraud; and (3) To investigate stages carried out in preventing the obstacles faced in the implementation of the Tri Kaya Parisudha concept as the prevention effort of accounting fraud. The research was carried out using a qualitative approach and descriptive types of approach. The data used were both primary and secondary, such as interviews, observation, documentation, and literature study. The results showed that the implementation of the Tri Kaya Parisudha concept as the prevention effort of accounting fraud potential in Aneka Lovina Hotel had been running well but some obstacles made its implementation had not run optimally.